Cayley graphs of order 16p are hamiltonian - Curran, Stephen J. (Ars mathematica contemporanea, 2012)
Suppose ?$G$? is a finite group, such that ?$|G| = 16p$?, where ?$p$? is prime. We show that if ?$S$? is any generating set of ?$G$?, then there is a hamiltonian cycle in the corresponding Cayley graph Cay?$(G; S)$?.
Keywords: Cayley graphs; Cayleyjevi grafi; graph theory; hamiltonian cysles; hamiltonski cikli; teorija grafov